A Community-Driven Analysis of Home Delivery Preference among Tribal Families in Bhimpur Block, Madhya Pradesh (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Despite the expansion of institutional maternal health services in India, home delivery remains prevalent among tribal communities. Socio-cultural traditions, geographical isolation, economic constraints, and trust in traditional birth attendants continue to influence childbirth practices. Understanding these factors is essential for designing culturally responsive maternal health interventions.Aim & Objectives: The study aimed to analyze the socio-cultural, geographical, economic, and trust-based factors influencing the preference for home delivery among tribal communities in the Bhimpur Block of Betul district, Madhya Pradesh. The objectives included assessing awareness of government maternal health schemes, access to health facilities, and the role of elders and traditional dais in childbirth decision-making.Materials & Methods: A cross-sectional descriptive study design was adopted. Purposive sampling was used to select 200 tribal elders from the villages of Guruwa, Pipariya, and Kasmarkhandi. Data was collected through face-to-face interviews using structured and semi-structured questionnaires. Descriptive statistics were employed for quantitative analysis, while thematic analysis was used for qualitative responses. Results: The findings revealed that 66% of respondents preferred home delivery. Cultural practices significantly influenced this preference (66%), along with a high level of trust in traditional dais (81%). Elders played a dominant role in childbirth decisions (90%). Awareness of ambulance services (82%) and the Janani Suraksha Yojana (64%) was moderate; however, only 29% were aware of a nearby delivery facility, and 61% perceived health facilities as geographically distant.Conclusion: The study concludes that the preference for home delivery is shaped by deeply rooted cultural norms, financial insecurity, limited accessibility, and trust-based relationships rather than mere personal choice. Culturally sensitive, decentralized maternal health strategies are essential to improve institutional delivery uptake in tribal regions.